Untimely matter in the time of Shakespeare - Harris, Jonathan Gil (UPCC book collections on Project MUSE., 2009)
Jonathan Gil Harris challenges the way we conventionally understand physical objects. Turning to Renaissance theories of matter, he considers the profound untimeliness of things, focusing particularly on Shakespeare's stage materials.